Evaluation of Euler’s Equation of Motion: Applications and Computation of Euler's Equation for Ideal Fluid Motion (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In this paper, Euler‟s equation of motion for steady flow of ideal fluid has been derived in orderto solve physical problems related to ideal incompressible fluid in motion. The equation is interesting as itrelates the velocity and pressure of fluid with density .The equation being computationally attractive andhas applications, one of which is demonstrated through example.